Kondisi Running-in pada Sliding Contact dengan Variasi Pelumas Berbahan Minyak Kelapa - Dedison Gasni; Brento Napitupulu (METAL: Jurnal Sistem Mekanik dan Termal, 2020)
Bathtube curves are often used by reability engineers to describe the life of a product's population. This graphical representation of the bathtube curve can be divided into 3 phases. The first phase of the curve is infant mortality failure which is characterized by decreasing failure rate. The second phase is normal life or useful life which the failure rate is aproximately constant. Finally, the third phase is wearout failures and it is assumed that failure rate increases. To observe the running-in periode, a pin on disc test was conducted based on the ASTM G99 standard, where the disk rotates and the pin is  loaded. So that the relative motion occurs between the pin and disk with a  point contact. Between the surface of the disk and the pin is lubricated with several types of lubricant. Tests carried out for 30 minutes with a time interval of data collection every 6 minutes. From the results of tests, in the phase of running-in periode shows that the wear rate in the first 6 minutes was very high and it tends to decrease exponentially. Lubricant could influence the wear rate and surface texture of the discs in the running-in periode as well.